POLA ASUH ANAK DI TENGAH PANDEMI COVID-19: Pendekatan Humanistik dalam mendukung Tumbuh Kembang Anak - Yusuf Effendi (UIN Sunan Kalijaga Yogyakarta, 2020)
The COVID-19 pandemi has made all children's activities ranging from teaching and learning activities to self-development to be carried out at home. Parents are required to be able to guide and facilitate all their children's needs to ensure that children can learn and develop well. For that we need a good parenting style and support the child's self development. The purpose of this study is to find a complete integration of parenting patterns based on Abraham Maslow's humanistic concept to ensure the fulfillment of children's needs amid the COVID-19 pandemi while ensuring that children develop well. This study uses a qualitative research method with a literature approach to collect, study and analyze a complete concept of parenting in the midst of a pandemic. This research found that the integration of humanistic concepts in parenting in the midst of the COVID-19 pandemi resulted in a holistic parenting concept by paying attention to several aspects such as the fulfillment of physiological needs, security, love and affection, self-esteem and culminating in self-actualization where children are capable. understand and develop self potential well. Keyword : COVID-19, Pandemi, Parenting, Humanistic Psychology